THE PART OF THE PRODUCTION FOREST MANAGEMENT UNIT TO THE REALIZING SUSTAINABLE FOREST MANAGEMENT AT THE SARMI REGENCY PROVINCE OF PAPUA - Hutabalian, Roida (Universitas Bengkulu, 2023)
This research to aims for to determine implementation of the Forest Management Production Unit role in realizing sustainable forest management in Sarmi Regency, and as well to find out the obstacles and solutions for unified Forest Management Production Unit in realizing sustainable forest management at the Sarmi Regency, Province of Papua. The method used in this research is sociological juridical research methods and/or empirical legal research. This method is used for the reason that in this research the emphasis is on legal science and the study of legal rules that apply in society related to forest management units. Sociological juridical research uses primary and secondary data. Primary data comes from interviews with sources and the public, while secondary data is obtained through references from literature studies in accordance with the title of this research. The results of the research show that, the role of the Forest Management Production Unit (KPHP) for region XXI across Sarmi and Memberamo Raya Regencies, on the one hand has made several positive contributions to economic development and regional development in Papua Province, but on the other hand the presence of KPHP has not had a direct impact on indigenous community around a forests, especially at site level. Likewise, the proposal for the formation of KPHP by the Sarmi Regency government to become a Regional Work Unit (SKPD), has not yet been realized due to many factors and indicators that must be met. Keywords : Role, Management Production Unit, Sustainable Forest Management.